Gerrard Winstanley's Theology of Creation: An Approval1 - Lindsey, William D. (Toronto journal of theology, 1988)
Studies of the seventeenth-century English theologian and political activist Gerrard Winstanley (1609 — 676) have usually taken one of two tacks: Winstanley is viewed as a theologian, and the radical political import of his theology is discounted; or he is interpreted as a political reformer who eventually repudiated his early theological works, and who eschewed theology for rational political analysis. Winstanley is remembered by historians primarily because of his radical 'digging' experiment. As a result of his theological convictions, he and his followers appropriated common land which had been enclosed by large landholders, and planted crops upon the land as a sign of protest against the enclosure of land and as a statement of the right of the dispossessed to the land. The movement which he founded, the 'Diggers', took its name from this digging experiment.